Visuals and text in pharmaceutical advertising: A multimodal analysis and ethical dilemmas - Svitlana Nasakina (Когниция, коммуникация, дискурс)
This article deals with the multimodality in modern English-language advertising. The influence of advertising on consumers has been a subject of many investigations among linguists. In this present paper, I build on the theoretical and practical data gained by researchers who studied virtual influencers in multimodal advertising, discussed the unique characteristics of the suggestion realization strategies in political advertising, evaluated advertisement discourse influence formula in terms of positive and negative orientation of the advertisement, investigated various functions of different contact languages in advertising, the phenomenon of multimodality in the Polish advertising of pharmaceutical products with the audio-visual spots. Scholars also used a pragmatic approach to advertisements in Britain and Japan and conducted a multimodal discourse analysis of malaria drugs advertisement. However, the role of multimodality in the context of pharmaceutical advertising remains understudied. Advertised pharmaceutical products have an impact on human consciousness. Misleading or inaccurate information can seriously affect consumers, including adverse health outcomes. The unique nature of pharmaceutical advertising makes pharmaceutical advertising different from other types of advertising, like political or consumer advertising. The material for this study consists of 500 samples in both paper and electronic formats. I hypothesize that the multimodal character of pharmaceutical advertising, incorporating both verbal and non-verbal elements, significantly enhances its persuasive impact by influencing consumer emotions and encouraging them to select specific pharmaceuticals. To prove this hypothesis, I identified patterns of interaction between verbal and non-verbal components through the prism of words, images, signs, and symbols. In this research, a multimodal approach allowed to uncover both the intended meanings and the subtle manipulation tactics used in pharmaceutical advertising.